Imperialismo na amazônia: os escândalos de Putumayo a partir da imprensa (1904-1912) - Amorim, Ravi Rodrigues (2024)
The region around the Putumayo River was the stage of intense conflict over boundaries since the end of the XIX century, between the recently institutionalized republics of South America. It became the target of economic and political interest from the most industrially developed imperialistic States from the period for its natural reserves of rubber plants that functioned as raw material responsible for the industrial boom of the Automobile Age. The present investigation aims to present the “Putumayo Scandals”, set of discourses that represent the process of violence and exploitation by a multinational enterprise, through the materialistic methodology and the conceptual reference of totality. The research analyzed a variety of historical sources that compose those discursive efforts, centering finally on the publications of two Brazilian journals, from which a reconstruction of discourse patterns and representation of chronological events is made. The Putumayo assumes archetypical characteristics of the exploratory process in the Amazon Forest and reveals the methods of domination instrumented in favor of the capitalist accumulation and the expansion of capital national boundaries. The analysis on the industry and the international rubber market makes up to a significant amount of the investigation here presented, inserting the events and the “scandals” in a broader frame of political and commercial disputes that grants meaning for the content addressed. In the investigation process, the perception of a structural chain of concrete determinations leaded to conclusions presented through, by one hand, the theory of imperialism, under the assumption of the totality logic, and, on the other hand, through the presentation of the vestiges and discourses in the journals that justifies and demonstrates the concretization of a transformative singular process on the international industrial capitalism into a dispute of imperialistic monopolies – process that dragged different parts of the world to a race of production and accumulation in benefit of a particular social class with access to progressively more sophisticated devices to subject territories and populations to their private control in a system increasingly capable of dominating through indirect and artificially impersonal mechanisms.